PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Coffeeshop Ruang Teduh Bireuen) - Ferdy Joely, Muhammad; Azhari, Azhari (Fakultas Ekonomi Universitas Almuslim Bireuen, 2024)
The research aims to analyze product purchasing decision factors from the aspects of product quality, service quality and location. Take the case at Ruang Teduh Bireuen Coffeeshop. Surbei research uses associative quantitative methods. Based on Roscoe's theory, the minimum sample size in this study was 40 respondents who had used the products at Ruang Teduh Bireuen Coffeeshop several times. The results are known; (1) factors that are thought to influence purchasing decisions from the product quality aspect have a direct and indirect influence of 47.21%, the service quality aspect is 36.92% and the location aspect of the Ruang Teduh Bireuen Coffeeshop is 54.66%. (2) The three predictor factors, namely product quality, service quality and location, are causally related. So, (3) simultaneously product quality, service quality and location make a real contribution of 50.1%. It is recommended that the management of Ruang Teduh Bireuen Coffeeshop conduct a survey about what things motivate consumers to make purchases, thereby increasing buyers' subjective norms in the expected direction.